Student mental health detection - Ningtyas, Claudia Dwi; Bistari, Bistari (Jurnal Ilmu Keolahragaan, 2024)
Adolescence is a stage of development that is very vulnerable to mental health problems. Adolescent mental health can be influenced by various factors, namely, gender, physical activity, transition from secondary to tertiary education, lack of mental health literacy, and lack of gratitude. This study aims to detect the mental health condition of university students. There are 4 indicators measured in the student mental health detection questionnaire, namely physical health, feelings, daily activities, and also mindset. The research method used is quantitative descriptive data collection method. The research subjects were starta-1 students from different universities, with 135 students as respondents. The instrument used was a questionnaire using google form which was distributed to all students via WhatsApp application. Data analysis using descriptive statistics. The results of this study indicate that physical health affects mental health. Most respondents are relevant to this. But in the indicators of feelings, daily activities, and mindset, many respondents were not relevant that these three indicators could affect mental health. This means that students are generally aware of the importance of mental health and try to maintain it.